2011
DOI: 10.1159/000330267
|View full text |Cite
|
Sign up to set email alerts
|

Origins and Breakpoint Analyses of Copy Number Variations: Up Close and Personal

Abstract: Array-based methods have enabled the detection of many genomic gains and losses. These are stated as copy number variants (CNVs) and comprise up to 13% of the human genome. Based on their breakpoints and modes of formation CNVs are termed recurrent or nonrecurrent. Recurrent CNVs are flanked by low copy repeats and are of a fixed size. They arise as a result of misalignment during meiosis by a mechanism named nonallelic homologous recombination. Several of such recurrent CNVs have been linked to human diseases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…adaptive amplification. One of the common mechanisms of such amplification is unequal crossing over that takes place between homologs or sister chromatids within the amplified region (van Binsbergen, 2011). The role of unequal meiotic recombination in the formation of many disease resistance gene clusters in crop plants has been documented ( Van der Hoorn et al, 2001;Nagy and Bennetzen, 2008;Luo et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…adaptive amplification. One of the common mechanisms of such amplification is unequal crossing over that takes place between homologs or sister chromatids within the amplified region (van Binsbergen, 2011). The role of unequal meiotic recombination in the formation of many disease resistance gene clusters in crop plants has been documented ( Van der Hoorn et al, 2001;Nagy and Bennetzen, 2008;Luo et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…NAHR during meiosis can generate rearrangements as a consequence of recombination between regions of high sequence homology like LCRs and dispersed Alu repetitive elements. 45 For CYP2A6 , the presence of two direct LCRs likely renders the region susceptible to rearrangements, leading to NAHR-mediated reciprocal full gene deletion and duplication. 22 As such, the different subtypes of the CYP2A6 deletion allele ( CYP2A6*4A-H ) previously reported in African populations 46 are likely the result of unique breakpoints mediated by different homologous Alu and/or other neighboring low complexity repeats.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the first example of AZF-linked CNVs generated by replication-based mechanisms. In this context, recent studies have shown that MMBIR is involved in several simple and complex rearrangements in the human genome [Zhang et al, 2009;van Binsbergen, 2011;Ottaviani et al, 2014]. Thus, it is possible that MMBIR represents a rare etiology of AZF-linked CNVs.…”
Section: Discussionmentioning
confidence: 99%
“…For example, NAHR between 2 human endogenous retroviral sequences underlies CNVs in the AZFa region [Kamp et al, 2000;Sun et al, 2000;Bosch and Jobling, 2003]. CNVs in the human genome are known to be caused not only by NAHR but also by microhomologymediated break-induced replication (MMBIR) and nonhomologous end joining (NHEJ) [Gu et al, 2008;Hastings et al, 2009;van Binsbergen, 2011]. MMBIR and NHEJ produce CNVs whose fusion junctions are accompanied by microhomologies and short nucleotide stretches, respectively [Hastings et al, 2009;Ottaviani et al, 2014].…”
mentioning
confidence: 99%